Danish development cooperation in fragile states - Erik Lundsgaarde (Danish Institute for International Studies (DIIS), 2019)
Addressing the complex challenges that fragile states face is an important area for action on the international development cooperation agenda. Danish development cooperation prioritizes countries that are considered fragile states. This DIIS Working Paper provides an overview of Danish aid to fragile states and reviews Danish aid delivery approaches in six countries: Afghanistan, Burkina Faso, Mali, Niger, Palestine, and Somalia. These countries are labelled as "poor, fragile" priority countries in Denmark's Strategy for Development Cooperation and Humanitarian Action. The paper focuses on cooperation modalities implemented through country programmes. While the country programmes include a mix of modalities tailored to the diverse contexts profiled, the paper points to a growing emphasis on multilateral organisations as implementation partners. This indicates potential for further analysis of the consequences of intermediated cooperation for aid management and development effectiveness. The paper also concludes that the complementarity between development cooperation administered inside and outside country programmes, and the clarification of activities contributing to conflict prevention goals are worthy of further study.
Keywords: 330